2009
DOI: 10.1007/s12311-009-0134-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Damage Loosens the Strategic Use of the Spatial Structure of the Search Space

Abstract: The influence of a hemicerebellar lesion on the exploration of environments with different spatial distributions of multiple rewards was analyzed. Hemicerebellectomized (HCbed) and intact rats were submitted to a search task in which they had to explore nine food trays in an open field, avoiding repeated visits. Trays were spatially arranged in four configurations: cross, 3 x 3 matrix, circle, and three clusters of three trays each. Lesioned and intact rats' performances improved in all configurations used. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Extensive anatomo-functional connections [62] support the interplay between the cerebellar and frontal areas that interact in executive control of voluntary behavior [63][64][65]: the cerebellum permits acquisition of efficient procedural competencies and the frontal cortex provides flexibility among already acquired and stored solutions [66][67][68]. Previously, we demonstrated that in rats HCb provokes lack of flexibility in changing strategy, impossibility to inhibit patently wrong responses [69][70][71], deficits due to impairment in adapting behavior to context. The evidence that the EH animals displayed no "frontal-like" deficits as perseverations and lack of attention to novel stimuli, as well as no deficient working memory, could be an index of an efficient use of cerebello-frontal networks.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive anatomo-functional connections [62] support the interplay between the cerebellar and frontal areas that interact in executive control of voluntary behavior [63][64][65]: the cerebellum permits acquisition of efficient procedural competencies and the frontal cortex provides flexibility among already acquired and stored solutions [66][67][68]. Previously, we demonstrated that in rats HCb provokes lack of flexibility in changing strategy, impossibility to inhibit patently wrong responses [69][70][71], deficits due to impairment in adapting behavior to context. The evidence that the EH animals displayed no "frontal-like" deficits as perseverations and lack of attention to novel stimuli, as well as no deficient working memory, could be an index of an efficient use of cerebello-frontal networks.…”
Section: Discussionmentioning
confidence: 99%
“…An environment organized in clusters allows to be explored with the possibility of chunking it, first visiting the locations within the same cluster and then moving to another one. The ''chunking theory'' predicts that once the chunks have been explored the burden on memory should be lightened from the total number of buckets to be explored (in our case, nine) to the number of clusters constituting the search space (in our case, three) (Foti et al, 2007(Foti et al, , 2010. Thus, the hierarchical organization of memory afforded by chunking substantially reduces the working memory load and promotes higher level performances (Terrace & McGonigle, 1994).…”
Section: Discussionmentioning
confidence: 93%
“…Efficient strategies for exploring the Matrix configuration are structured search patterns that follow rows (or columns) sequentially or, conversely, that travel the perimeter of the external ''square'' to reach the most internal bucket at the end. When the strategic use of these searching patterns is loosened, a compromise between an explorative behavior promoting an extended search among rewarded buckets (i.e., visiting buckets farther away than those previously visited or following diagonal trajectories between buckets) and a behavior that limits the information to be stored (i.e., visiting the nearest bucket) may be used (Foti et al, 2007(Foti et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations